Kualiti air sungai berdasarkan analisis kimia dan kepelbagaian alga - Kasan, Nor Azman (2006)
Sungai Pontian Kecil is used by villagers around Pontian District for their daily activities such as water supply for irrigation, fisheries and recreation. Study on Sungai Pontian Kecil was conducted during non-raining and raining months. The level of water pollution was determined based on Water Quality Index (WQI) and Shannon-Weiner Index (H’). The relationship between both indexes was evaluated. The land use activities that contributed to the decline of water quality of the river include discharge of wastewater, agricultural activities and settlements along the river corridor. Chemical analysis of the river water was used to determine WQI value. Besides that, H’ value was based on the classification of algae. Results showed that there is a relationship between WQI and H’ where water quality at the upstream is Class II during non-raining month with 75 and 3.08 respectively, while during raining month the WQI and H’ were 85 and 2.90 respectively, indicating clean water quality during both months. On the other hands, water quality at the downstream is Class IV with 38 and 1.42 respectively during non-raining month, while 35 and 1.20 respectively during raining month, indicating polluted water quality. The presence of large amount of Bacillariophyceae and Chlorophyceae classes indicated clean water quality, while the presence of Euglenophyceae and Cyanophyceae classes indicated pollution. It was found that Navicula sp. was the dominant algae species during both non-raining and raining months. Algae cell calculation at the upstream was high with 8870 cell/mL and 7828 cell/mL respectively compared to the downstream with 1138 cell/mL and 353 cell/mL respectively during both months. As a conclusion, polluted water quality influences algae populations in the river where algae populations are high at clean water quality.